2008
DOI: 10.1007/s11255-008-9377-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma after living donor kidney transplantation: an Iranian multicenter experience

Abstract: PTLD is a major threat to kidney transplant recipients. Immunosuppressive agents have a significant role in developing the disease. Early detection of the disease and using more safe immunosuppresants may have beneficial effects on patient outcomes and incidence of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This study indicated that the prognosis of transplant recipients with m-PTLD was still poor, with a 5-year survival rate of 59.2%; this was similar to those reported by Lawrence R et al who found a 5-year survival rate in B-cell m-PTLD patients of approximately 53%, and Vahid Pourfarziani et al who observed a 5-year survival rate of 59% in m-PTLD recipients after KT [16,17]. Although most deaths were associated with progressive disease, up to 60% of patients would eventually die from unrelated cause (mainly infections), emphasizing the vulnerability of transplant patients, even in complete remission.…”
Section: Discussionsupporting
confidence: 88%
“…This study indicated that the prognosis of transplant recipients with m-PTLD was still poor, with a 5-year survival rate of 59.2%; this was similar to those reported by Lawrence R et al who found a 5-year survival rate in B-cell m-PTLD patients of approximately 53%, and Vahid Pourfarziani et al who observed a 5-year survival rate of 59% in m-PTLD recipients after KT [16,17]. Although most deaths were associated with progressive disease, up to 60% of patients would eventually die from unrelated cause (mainly infections), emphasizing the vulnerability of transplant patients, even in complete remission.…”
Section: Discussionsupporting
confidence: 88%
“…MMF is reported to be associated with primary central nervous system lymphomas, and azathioprine has been associated with lymphoproliferative disorders. [89][90][91] In a study of patients after renal transplantation, the 10-year cumulative incidence of first cancer, first skin cancer, and first solid organ cancer was 24.6%, 14.5%, and 14.5%, respectively. There was no significant difference between the immunosuppressive drugs used.…”
Section: Opportunistic Infections Malignancies and Immunosuppressivmentioning
confidence: 99%
“…Reported reasons for this high incidence include EpsteinBarr virus (EBV) infection, greater levels of immunosuppression, and use of OKT3, antilymphoblast globulin (ALG), and antithymocyte globulin (ATG) [5][6][7]. Investigators have suggested that the incidence, time interval, presentation, and prognosis of PTLD vary depending on the organ transplanted, recipient age, and immunosuppression intensity [8][9][10][11][12][13][14][15][16]. The reported incidence of PTLD in liver recipients ranges from 1.7 to 9%, with most cases occurring within the first 1.5 years after transplantation [2][3][4][5][6][7][17][18][19].…”
Section: Introductionmentioning
confidence: 99%